Penguatan Lembaga Kehakiman Sebagai Salah Satu Upaya Perbaikan Kualitas Hukum di Indonesia - Indah Febriani; Theta Murty (Universitas Sriwijaya, 2019)
In the process of law enforcement, the three elements in the legal system have a vital role. One of them is the element of the legal structure especially the judge. Strengthening the judiciary is one of the main pillars in creating a clean and authoritative judiciary, but in reality, the judges act out of expectations, the judge acts not neutral, is not free so that public trust in the judges and judiciary institutions disappears. The problem is how efforts can be made in realizing a clean and authoritative judiciary. Efforts can be made, among others, the Judge as one of the parts of law enforcement has a central position in the law enforcement process, so that the judges should have superior quality, so as to produce a fair decision. The superiority of the quality of judges can be realized by various efforts, including improving the pattern of recruitment, selection, and education of judges, improving the payroll system and retirement benefits, and improving the pattern of supervision. If these things are carried out continuously, it is expected to have a positive impact on efforts to strengthen the judiciary in general as a forum for judges.